2017
DOI: 10.4049/jimmunol.1601282
|View full text |Cite
|
Sign up to set email alerts
|

Early Phase Mast Cell Activation Determines the Chronic Outcome of Renal Ischemia–Reperfusion Injury

Abstract: Ischemia–reperfusion injury (IRI) is an important cause of acute kidney injury that can lead to end-stage renal failure. Although the ensuing inflammatory response can restore homeostasis, a consecutive maladaptive repair and persistent inflammation represent important risk factors for postischemic chronic kidney disease development. In this study, we investigated the role of mast cells in both the early and late phases of the inflammatory response in experimental models of acute and chronic renal IRI using ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 59 publications
(69 reference statements)
2
25
1
Order By: Relevance
“…We have also analyzed possible cytokines involved in this transition such as TGFβ (41) and IL6 (40). We found that stimulation of cultured MCs via the IgE receptor can induce the production of these cytokines in agreement with previously published data (47, 58). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We have also analyzed possible cytokines involved in this transition such as TGFβ (41) and IL6 (40). We found that stimulation of cultured MCs via the IgE receptor can induce the production of these cytokines in agreement with previously published data (47, 58). …”
Section: Discussionsupporting
confidence: 93%
“…These results add to a series of studies showing on the role of MC in fibrosis development. While some reported that MC promote fibrosis development (22, 44, 46, 47) as shown here, others suggested that MC or derived mediators can have a protective role (14, 19). These differences may be explained by the specific pathophysiological context with different types of injuries but also disease kinetics.…”
Section: Discussionmentioning
confidence: 50%
“…However, detection of MC‐tryptase in renal draining LNs of mice with glomerulonephritis has been described . In addition, murine MCs expressing connectival‐like proteases such as MCPT‐6 and MCPT‐4 have been described to localize in the renal capsules, where they showed pattern of degranulation in the setting of renal inflammation . Although the number of reports studying MC activation in experimental models of renal diseases is increasing, the knowledge about the involved mediators is still limited.…”
Section: Kidney Mast Cellssupporting
confidence: 65%
“…Using MC‐deficient mice, several animal models of renal diseases have revealed a more complex scenario, with both aggravating and protective roles of the MC, depending on the experimental model but also on the employed MC‐deficient mouse strain . MCs are virtually absent in the parenchyma of mouse kidneys but, in contrast with human chronic diseases, they have not been found infiltrating fibrotic kidneys in different models . In rats, several reports suggested that renal fibrosis instauration is accompanied by MC infiltration .…”
Section: Kidney Mast Cellsmentioning
confidence: 98%
“…Consistent with an important role for mast cells in kidney injury, a recent study showed that mast cell ablation in the early phases of renal injury is sufficient to reduce subsequent fibrosis by decreasing the inflammatory response. 27,28 Activation of Epithelial, Endothelial, and Stromal Cells in Allograft Rejection We next compared epithelial transcriptomes from the biopsy with their healthy counterparts. Multiple attempts at scRNAseq of healthy nephrectomy tissue failed to generate libraries; however, we were successful in generating adult human kidney single-nucleus RNA-sequencing (RNA-seq) data.…”
Section: Comparative Analysis Reveals Monocyte Cell-state Transition mentioning
confidence: 99%